The Relationship Between Organizational Climate and Teacher Job Satisfaction at Madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung - Sri Rahayu Nasution; Qomaruddin Lubis; Rija Ansyari; Elfin Nazri; Muhammad Rizki Dermawan Saragih (STAI Miftahul Ula Nganjuk, 2022)
The problem in this study is whether there is a relationship between the organizational climate and teacher job satisfaction. What is the organizational climate in madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung. How is the job satisfaction of teachers in Madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung. Based on the above problems, the purpose of this study is to determine the organizational climate in madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung, to find out the job satisfaction of teachers in Madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung and to find out the relationship between the organizational climate and teacher job satisfaction in Madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung. To study the above problems, the author used quantitative data processing, the author's sample determined as many as 30 people which were carried out at the Private Tsanawiyah Madrasah PAB 1 Sampali because they had the same characteristics as population schools. Sampling was carried out outside the population because in madrasah Tsanawiyah Al-Jam'iyatul Washliyah Tembung there were only 57 people, to find out the extent of the relationship between the organizational climate and teacher job satisfaction, the product moment correlation formula was used. From the results of calculating the Product Moment correlation between the organizational climate variable (X) and the teacher job satisfaction variable (Y), an rxy of 0.806 was obtained and at a significance level of 5% was obtained rtable 0.266, thus rcalculation greater than rtable (0.806 > 0.266). Ho is rejected while Ha is accepted this means that there is a significant relationship between the organizational climate variable (X) and the teacher job satisfaction variable (Y).